METABOLIC PLATELET STATUS IN PATIENTS WITH STABLE ANGINA - I. Yu. Grinstein; A. A. Savchenko; E. A. Savchenko; A. A. Kosinova; Yu. I. Grinstein (Российский кардиологический журнал, 2013)
Aim. To study the activity of NAD- and NADP-dependent platelet dehydrogenases in patients with various functional classes of angina. Material and methods. The study included 91 men with Functional Class II–IV angina, aged 45–72 years. In all participants, the bioluminescent method was used to measure the activity of the following enzymes: glucose-6-phosphate dehydrogenase (G6PD), glycerol-3-phosphate dehydrogenase (GPDH), NADPmalate dehydrogenase (NADP-MDH), NAD- and NADH-dependent lactate dehydrogenase reaction (LDH and NADH-LDH, respectively), NAD- and NADHdependent malate dehydrogenase reaction (MDH and NADH-MDH, respectively), NADP- and NADPH-dependent glutamate dehydrogenase (NADP-GDH and NADPH-GDH, respectively), NAD- and NADH-dependent glutamate dehydrogenase (NAD-GDH and NADH-GDH, respectively), NAD- and NADP-dependent isocitrate dehydrogenase (NAD-IDH and NADP-IDH, respectively), and glutathione reductase (GR). Results. The metabolic platelet status was associated with the functional class of angina. In patients with Functional Class II angina, minimal platelet changes, linked to the inhibition of plastic processes, were observed. Patients with Functional Class III angina demonstrated an inhibition of lipid metabolism and an increase in glycolytic activity. In Functional Class IV angina, the metabolic disturbances were most pronounced and manifested in inhibited plastic processes and lipid catabolism, together with activated anaerobic reactions. Conclusion. In stable angina patients, the changes in intracellular metabolic activity of platelets mirror the increase in the functional class of angina. Modification of platelet metabolism could be one of the methods of decreasing the receptor and, therefore, aggregation platelet activity.